Transitioning from cytology-based screening to HPV-based screening at longer intervals: implications for resource use. Issue 1 (December 2016) - Smith, Megan; Gertig, Dorota; Hall, Michaela; Simms, Kate; Lew, Jie-Bin; Malloy, Michael; Saville, Marion; Canfell, Karen
Abstract Background Following a recent major review of cervical screening, from 2017 Australia will transition from two-yearly cytology-based screening to five-yearly primary HPV screening, with partial genotyping and direct referral for HPV 16/18 and LBC triage for other oncogenic types. Switching to a longer screening interval will result in transitional fluctuations for volumes of tests before a 'steady state' is reached for the new test volumes. This study aimed to quantify the impact of this transition on year-to-year volumes of screening and follow-up tests and procedures. Methods Number of women screened and test volumes from 2015 to 2032 were estimated via a detailed simulation model which explicitly modelled varying screening and HPV vaccination exposure in individual birth cohorts, and fully incorporated how a relatively rapid screening program switch in 2017 would affect both women attending for routine screening and those in surveillance following an abnormality. Results Numbers of women screened and HPV tests are predicted to fluctuate in the first screening rounds as a result of the transition to a longer screening interval (mean women screened and HPV tests 1.4 million in the first 5-year period, year-to-year fluctuation > +/−50 %; mean 1.5 million women/HPV tests in third 5-year period, fluctuation approximately +/−25 %). The extent to which this fluctuation was predicted to carry through to secondary tests/procedures was less (fluctuations of +25 %/-31 % in first 5-year period; decreasing to +8 %/-10 % by third round). HPV vaccination is predicted to counteract increases in high grade cytology results, colposcopies and precancer treatments which would otherwise occur due to population increases. Precancer treatments are predicted to drop below 2015 levels within the first few years of program switchover. Mean colposcopy volumes are predicted to be similar to 2015 levels by the third round of HPV-based screening, and also be 25–40 % lower than would have occurred in the absence of HPV vaccination. Conclusions While numbers of women attending for screening and HPV tests are anticipated to initially fluctuate as a result of the transition to a longer recommended interval, there is expected to be less fluctuation in follow-up tests and procedures; however these will still have a significant impact on operational aspects of the screening program. Detailed modelling of the switchover process gave important insights into how volumes would be affected.